Clinical Relevance of House Dust Mites as Causative Factor of Atopic Dermatitis in Surabaya-Indonesia - Sylvia Anggraeni; Bella Ayu Paramitha; Wisnu Triadi Nugroho; Menul Ayu Umborowati; Damayanti Damayanti; Anang Endaryanto; Cita Rosita Sigit Prakoeswa (Universitas Muhammadiyah Yogyakarta, 2021)
Atopic dermatitis (AD) is chronic inflammation of skin manifested as recurrent itchy redness patches. Avoiding precipitating factors is significant key of successful treatment, but not always possible. House dust mites (HDM) are the most common but not easily proven as aeroallergen. Skin prick test (SPT) is an effective diagnostic modality in recognizing type 1 hypersensitivity reaction. Positive result on SPT should be confirmed by clinical relevance to find the true causative factor. The aim of the study was to analyze the clinical relevance of HDM as AD causative factor in Surabaya, Indonesia. This is a descriptive observational study. Sixty samples were taken from SPT medical records in Allergy-Immunology Division outpatient care at Dr. Soetomo General Academic Hospital period of 2017 - 2019. All samples that qualify inclusion criteria were included. Data were compiled in data sheet, categorized as nominal, and presented as clinical relevance. This study reported that AD is more common in 21-30 years old (70%), Javanese (93.33%), female (783.3%). Most of them had history of itchy redness patches (83.33%), dry skin (55%), self and family history of atopic disease (93.33%; 53.33%). History of suspected HDM allergen was 50%, positive SPT results were 68,33%. Clinical relevance had shown that in 37 patients (61,67%), 17 out of 23 (73.92%) patients did not suspect HDM as allergen but has positive SPT results. It may conclude that HDM should be considered as hidden potent causative factor of AD in Surabaya, Indonesia.